A Novel Triculture System (CC3) for Simultaneous Enzyme Production and Hydrolysis of Common Grasses through Submerged Fermentation - Leo, Vincent V.; Passari, Ajit K.; Joshi, J. Beslin; Mishra, Vineet K.; Uthandi, Sivakumar; Ramesh, N.; Gupta, Vijai K.; Saikia, Ratul; Sonawane, Vijay C.; Singh, Bhim P. (Frontiers in Microbiology, 2016)
The perennial grasses are considered as a rich source of lignocellulosic biomass, making it a second generation alternative energy source and can diminish the use of fossil fuels. In this work, four perennial grasses Saccharum arundinaceum, Panicum antidotale, Thysanolaena latifolia and Neyraudia reynaudiana were selected to verify their potential as a substrate to produce hydrolytic enzymes and to evaluate them as second generation energy biomass. Here, cellulase and hemi-cellulase producing three endophytic bacteria (Burkholderia cepacia BPS-GB3, Alcaligenes faecalis BPS-GB5 and Enterobacter hormaechei BPS-GB8) recovered from N. reynaudiana and S. arundinaceum were selected to develop a triculture (CC3) consortium. During 12 days of submerged cultivation, a 55-70% loss in dry weight was observed and the maximum activity of β-glucosidase (5.36 to 12.34 IU) and Xylanase (4.33 to 10.91 IU) were observed on 2nd and 6th day respectively, whereas FPase (0.26 to 0.53 IU) and CMCase (2.31 to 4.65 IU) showed maximum activity on 4th day. Around 15-30% more enzyme activity was produced in CC3 as compared to monoculture (CC1) and coculture (CC2) treatments, suggested synergetic interaction among the selected three bacterial strains. Further, the biomass was assessed using Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The FTIR analysis provides important insights into the reduction of cellulose and hemicellulose moieties in CC3 treated biomass and SEM studies shed light into the disruption of surface structure leading to access of cellulose or hemicelluloses microtubules. The hydrolytic potential of the CC3 system was further enhanced due to reduction in lignin as evidenced by 1-4% lignin reduction in biomass compositional analysis. Additionally, laccase gene was detected from A. faecalis and E. hormaechei which further shows the laccase production potential of the isolates. To our knowledge, first time we develop an effective endophytic endogenous bacterial triculture system having potential for the production of extracellular enzymes utilizing S. arundinaceum and N. reynaudiana as lignocellulosic feedstock.